2018
DOI: 10.3847/2041-8213/aaeda9
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution SOFIA/EXES Spectroscopy of SO2 Gas in the Massive Young Stellar Object MonR2 IRS3: Implications for the Sulfur Budget

Abstract: Sulfur has been observed to be severely depleted in dense clouds leading to uncertainty in the molecules that contain it and the chemistry behind their evolution. Here, we aim to shed light on the sulfur chemistry in young stellar objects (YSOs) by using high-resolution infrared spectroscopy of absorption by the ν 3 rovibrational band of SO 2 obtained with the Echelon-Cross-Echelle Spectrograph on the Stratospheric Observatory for Infrared Astronomy. Using local thermodynamic equilibrium models we derive physi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
4
13
1
Order By: Relevance
“…Similar to our conclusion, Barr et al (2020) find that the MIR probes hot gas at the center of hot cores, compared to the sub-millimeter which probes the outer envelope. Two previous studies also show that SOFIA/EXES detects molecules previously unobserved at longer wavelengths (Barr et al 2018;Dungee et al 2018).…”
Section: Interpretation Of Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Similar to our conclusion, Barr et al (2020) find that the MIR probes hot gas at the center of hot cores, compared to the sub-millimeter which probes the outer envelope. Two previous studies also show that SOFIA/EXES detects molecules previously unobserved at longer wavelengths (Barr et al 2018;Dungee et al 2018).…”
Section: Interpretation Of Resultsmentioning
confidence: 66%
“…Currently, this is the only spectrograph able to resolve individual molecular transitions over the entire MIR. Several studies of hot cores with SOFIA/ EXES are ongoing (Indriolo et al 2015a(Indriolo et al , 2020Barr et al 2018Barr et al , 2020Dungee et al 2018). Rangwala et al (2018) detected eight HCN R-branch rovibrational transitions toward IRc2 between 12.96 and 13.33 μm, enough to directly calculate its temperature and column density.…”
Section: Introductionmentioning
confidence: 99%
“…The recent detection of several new sulfur-bearing molecules in the interstellar medium (ISM) (Agundez et al 2018;Cernicharo et al 2018), as well as in comet 67P/Churyumov-Gerasimenko (67P/C-G) by the Rosetta orbiter (Calmonte et al 2016) has, in part, spurred renewed interest in the chemistry of this malodorous element (Hudson & Gerakines 2018;Morgan et al 2018;Dungee et al 2018;Danilovich et al 2018;Drozdovskaya et al 2018;Zakharenko et al 2019;Gorai et al 2017).…”
mentioning
confidence: 99%
“…This study focuses on AFGL 2136 and AFGL 2591, however several other hot cores have been observed before at high spectral resolution at MIR wavelengths using a few specifically chosen settings. These studies reveal MIR transitions in absorption towards hot cores (Mitchell et al 1989(Mitchell et al , 1990Evans et al 1991;Knez et al 2009;Barentine & Lacy 2012;Rangwala et al 2018;Dungee et al 2018;Indriolo et al 2013Indriolo et al , 2015Indriolo et al , 2020. Hot cores have also been observed at low spectral resolution in the MIR with ISO (Lahuis & van Dishoeck 2000;Keane et al 2001;.…”
Section: Molecular Absorption Lines In the Ir Spectra Of Massive Prot...mentioning
confidence: 93%